2020
DOI: 10.3390/foods9101392
|View full text |Cite
|
Sign up to set email alerts
|

Flesh ID: Nanopore Sequencing Combined with Offline BLAST Search for the Identification of Meat Source

Abstract: Detection of animal species in meat product is crucial to prevent adulterated and unnecessary contamination during processing, in addition to avoid allergy and religious consequences. Gold standard is the real-time PCR assays, which has a limited target capability. In this study, we have established a rapid sequencing protocol to identify animal species within hours. Sequencing was achieved by nanopore sequencing and data analysis via offline BLAST search. The whole procedure was conducted in a mobile suitcase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
(28 reference statements)
0
2
0
Order By: Relevance
“…In this study, we found that only one SP used 4th GS with Oxford Nanopore technologies, and, accordingly, the full DNA barcodes were used (Ho et al., 2020). Until now, the available studies applying the Oxford Nanopore Technologies to food matrices especially rely on experimental mixtures to test the method efficiency (Kissenkotter et al., 2020; Rodríguez et al., 2023). No SPs used instead 3rd GS technologies.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we found that only one SP used 4th GS with Oxford Nanopore technologies, and, accordingly, the full DNA barcodes were used (Ho et al., 2020). Until now, the available studies applying the Oxford Nanopore Technologies to food matrices especially rely on experimental mixtures to test the method efficiency (Kissenkotter et al., 2020; Rodríguez et al., 2023). No SPs used instead 3rd GS technologies.…”
Section: Resultsmentioning
confidence: 99%
“…This technique has been used extensively for microbial sequencing but less so for meat species identification. For this reason, Kissenkötter, Böhlken‐Fascher, and El Wahed (2020a) combined this technology with an offline BLAST search tool to identify horse, chicken, turkey, beef, sheep, duck, rabbit, goat, and donkey in meat products. In their research, the accuracy, sensitivity, and speed of the nanopore sequencing technology were established within the first hour of base calling.…”
Section: Dna‐based Methods For Game Species Identificationmentioning
confidence: 99%